Branding de marca no processo gráfico artesanal de embalagens - estudo de caso: Loja dos Mimos. - Santos, Mariana Gemaque dos (Brasil, 2022)
This paper seeks to present ways in which the design, more specifically the packaging design, along with branding, can collaborate with the valorization of the company's identity adding value to products and services before its competitors, through a proposal of application of the identity in a handmade way. The development of this project required a bibliographic survey about themes such as: packaging functions, branding fundamentals and handmade graphic processes, in order to understand the relationships between them and their applications. The methodology applied was based on the fundamentals of design thinking, by Tim Brown (2008), contained in his book Design Thinkin - A powerful methodology to decree the end of old ideas. In addition, interviews and brainstorming meetings were held to help define which characteristics should be considered in the development of the final product, in order to obtain a strong brand identity application that contributes to the valuation and differentiation of the case study Loja dos Mimos in the market.